Dynamic Capability Approach to Pharmaceutical Transformation : Does organizational culture affect the development of dynamic capabilities? - Räsänen, Oliver (My University, 2025)
The pharmaceutical industry is undergoing significant transformation, as the traditional model centered on the development of blockbuster drugs is increasingly challenged by economic, regulatory, and technological pressures. Concurrently, the sector has exhibited a relatively slow pace in adopting digital innovations, with operational models in some areas still reflecting principles of the second industrial revolution. In response to these challenges, the dynamic capabilities framework has been proposed as a means to enhance organizational adaptability and responsiveness. However, questions remain regarding the applicability and development of such capabilities in highly regulated, traditionally structured environments such as the pharmaceutical industry. This study contributes to the literature by extending the microfoundations theory of capabilities, which posits that capabilities are developed through individual actions shaped by organizational structures and processes. Specifically, the study investigates how dimensions of organizational culture, innovativeness, trust, teamwork, and knowledge sharing, relate to the development of dynamic capabilities. A quantitative survey was administered in a single pharmaceutical case organization, and the data were analysed using Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM). The results indicate an acceptable model fit. Innovativeness was found to have a strong positive association with dynamic capabilities, while trust exhibited a negative relationship. Teamwork and knowledge sharing yielded mixed results, with partial empirical support. These findings provide empirical insights into the role of cultural factors in dynamic capability development and suggest practical implications for pharmaceutical organizations aiming to enhance adaptability through cultural transformation.

Lääketeollisuus on voimakkaassa muutoksessa, sillä taloudelliset, lainsäädännölliset ja teknologiset paineet haastavat perinteistä mallia, jossa keskitytään erittäin tuottavien, mutta lyhyen elinkaaren lääkkeiden (eng. blockbusters) kehittämiseen. Samanaikaisesti ala on omaksunut digitaalisia innovaatioita suhteellisen hitaasti, ja jotkin alan toimintamallit heijastavat edelleen toisen teollisen vallankumouksen periaatteita. Vastauksena näihin haasteisiin on ehdotettu dynaamisten kyvykkyyksien viitekehystä. Dynaamiset kyvykkyydet viittaavat keinoihin parantaa organisaation sopeutumis- ja reagointikykyä muuttuvaan ympäristöön. On kuitenkin edelleen epäselvää, ovatko tällaiset kyvykkyydet sovellettavissa ja kehitettävissä vahvasti säännellyissä ja usein rakenteellisesti jäykissä ympäristöissä, kuten lääketeollisuudessa. Tämä tutkimus täydentää kirjallisuutta laajentamalla kyvykkyyksien mikrotekijöitä koskevaa teoriaa, jonka mukaan kyvykkyyksiä kehitetään organisaation rakenteiden ja prosessien muokkaamien yksilöllisten toimien kautta. Tutkimuksessa tarkastellaan erityisesti, miten organisaatiokulttuurin ulottuvuudet, innovatiivisuus, luottamus, tiimityö ja tiedon jakaminen, liittyvät dynaamisten kyvykkyyksien kehittymiseen. Kvantitatiivinen kyselytutkimus toteutettiin yhdessä lääketeollisuuden organisaatiossa, ja tiedot analysoitiin käyttämällä konfirmatorista faktorianalyysiä (CFA) ja rakenneyhtälömallia (SEM). Tulokset osoittavat mallin sopivan aineistoon kohtuullisella tasolla. Innovatiivisuus selittää vahvasti dynaamisten kyvykkyyksien esiintymistä, kun taas yllättäen luottamus selitti dynaamisia kyvykkyyksiä negatiivisesti. Tiimityöskentely ja tiedon jakaminen saivat osittaista empiiristä tukea. Nämä havainnot tarjoavat empiiristä näyttöä kulttuuristen tekijöiden roolista dynaamisten kyvykkyyksien kehityksessä ja viittaavat käytännön toimenpiteisiin, joilla lääketeollisuuden organisaatiot voivat parantaa sopeutumiskykyään uusiin toimintamalleihin ja digitalisaatioon kulttuurisen muutoksen avulla.
Keywords: dynamic capabilities, pharmaceutical industry, microfoundations theory, organizational culture, Pharma 4.0, dynaamiset kyvykkyydet, lääketeollisuus, kyvykkyyksien mikrotekijät, organisaatiokulttuuri, Pharma 4.0